Present State of the Medical Expert System CADIAG-2 - Adlassnig, K.-P.; Kolarz, G.; Scheithauer, W. (Methods of Information in Medicine, 1985)
Uncertainty of knowledge about the patient and about medical relationships is generally accepted and considered to be an inherent concept in medicine. The physician, however, is quite capable of drawing conclusions from this information. Naturally, these conclusions are approximate rather than precise.Fuzzy set theory provides the possibility of defining imprecise medical entities as fuzzy sets. It offers a linguistic concept with excellent approximation to medical texts. In addition, fuzzy logic presents powerful reasoning methods that can handle approximate inferences. These facts make fuzzy set theory highly suitable for the development of computer-based medical diagnostic systems.The medical expert system CADIAG-2 provides evidence that fuzzy set theory is a suitable mathematical tool for formalizing medical processes.CADIAG-2/RHEUMA is being extensively tested on cases from a rheumatological hospital. Results from 327 cases are presented. In 265 cases, i.e. 81%, the clinical diagnosis could be either confirmed (223 cases, i.e. 68.2%) or established as a diagnostic hypothesis (42 cases, i.e. 12.8%).CADIAG-2/PANCREAS was tested on 47 cases of pancreatic diseases. In 43 cases, i.e. 91.5%, the clinical diagnosis was either confirmed by CADIAG-2 or established as one of the hypotheses with the highest or second highest number of points in a ranked list of hypotheses.
Keywords: Medical Expert System CADIAG-2; Fuzzy Set Theory; Rheumatology; Pancreatic Diseases